2009
DOI: 10.1519/jsc.0b013e31818cc65d
|View full text |Cite
|
Sign up to set email alerts
|

Effects of Dynamic and Static Stretching on Vertical Jump Performance and Electromyographic Activity

Abstract: The results of previous research have demonstrated that static stretching (SS) can reduce muscular performance and that dynamic stretching (DS) can enhance muscular performance. The purpose of this study was to assess the effects of SS and DS on vertical jump (VJ) performance and electromyographic (EMG) activity of the m. vastus medialis. Eleven healthy men (age 21 +/- 2 years) took part in 3 conditions (no stretching [NS], SS, and DS), on separate occasions in a randomized, crossover design. During each condi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

5
103
1
17

Year Published

2010
2010
2018
2018

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 159 publications
(141 citation statements)
references
References 22 publications
5
103
1
17
Order By: Relevance
“…The most common method is static stretching, which places muscles in their lengthened positions and maintains the positions for a certain period of time (Kisner, performances as leg extension power (Yamaguchi and Ishii, 2005), vertical jump height (Hough et al, 2009), and golf swing performance (Moran et al, 2009). Although dynamic stretching is now gaining recognition as an effective exercise for improving sports performance, precisely what happens to the muscle-tendon unit (MTU) is still unclear.…”
Section: Introductionmentioning
confidence: 99%
“…The most common method is static stretching, which places muscles in their lengthened positions and maintains the positions for a certain period of time (Kisner, performances as leg extension power (Yamaguchi and Ishii, 2005), vertical jump height (Hough et al, 2009), and golf swing performance (Moran et al, 2009). Although dynamic stretching is now gaining recognition as an effective exercise for improving sports performance, precisely what happens to the muscle-tendon unit (MTU) is still unclear.…”
Section: Introductionmentioning
confidence: 99%
“…Also stretching exercises increase in muscle compliance which may limit the more cross bridge coupling thus force production capacity of muscle decreases after stretching (Rubini et al, 2007). Neurologically, static stretching may cause decrease in muscle activation (Hough et al, 2009). Fowles et al (2000) reported that motor unit activation significantly decreased after prolonged (30 min) stretching.…”
Section: Discussionmentioning
confidence: 99%
“…Active recovery and stretching between the consecutive sets are mostly used by athletes and coaches to diminish the effects of fatigue. Previous studies demonstrated that static stretching has negative effects on performance which performed after static stretching (Cornwell et al, 2002;Evetovich et al, 2003;Hough et al, 2009;Kistler et al, 2010;Kokkonen et al, 1998;Nelson et al, 2005;Paradisis et al, 2014;Pinto et al, 2014;Young and Behm, 2003). However, little research has reported the effects of stretching between sets on the number of repetitions or volume completed.…”
Section: Introductionmentioning
confidence: 97%
“…However, many authors reported that the use of static stretching before maximal physical activity may temporarily reduce force and power production [5][6][7], vertical jump performance [8][9][10] and running speed [11,12]. In contrast, other studies have observed no detrimental effects of static stretching in selected neuromuscular parameters [13][14][15][16].…”
mentioning
confidence: 99%